Insight into the microbial world of Bemisia tabaci cryptic species complex and its relationships with its host - Wang, Hua-Ling; Lei, Teng; Xia, Wen-Qiang; Cameron, Stephen L.; Liu, Yin-Quan; Zhang, Zhen; Gowda, Maruthi M. N.; Navas-Castillo, Jesús; Omongo, Christopher A.; Delatte, Hélène; Lee, Kyeong-Yeoll; Patel, Mitulkumar V.; et al. (Springer Nature, 2019)
The 37 currently recognized Bemisia tabaci cryptic species are economically important species and contain both primary and secondary endosymbionts, but their diversity has never been mapped systematically across the group. To achieve this, PacBio sequencing of full-length bacterial 16S rRNA gene amplicons was carried out on 21 globally collected species in the B. tabaci complex, and two samples from B. afer were used here as outgroups. The microbial diversity was first explored across the major lineages of the whole group and 15 new putative bacterial sequences were observed. Extensive comparison of our results with previous endosymbiont diversity surveys which used PCR or multiplex 454 pyrosequencing platforms showed that the bacterial diversity was underestimated. To validate these new putative bacteria, one of them (Halomonas) was first confirmed to be present in MED B. tabaci using Hiseq2500 and FISH technologies. These results confirmed PacBio is a reliable and informative venue to reveal the bacterial diversity of insects. In addition, many new secondary endosymbiotic strains of Rickettsia and Arsenophonus were found, increasing the known diversity in these groups. For the previously described primary endosymbionts, one Portiera Operational Taxonomic Units (OTU) was shared by all B. tabaci species. The congruence of the B. tabaci-host and Portiera phylogenetic trees provides strong support for the hypothesis that primary endosymbionts co-speciated with their hosts. Likewise, a comparison of bacterial alpha diversities, Principal Coordinate Analysis, indistinct endosymbiotic communities harbored by different species and the co-divergence analyses suggest a lack of association between overall microbial diversity with cryptic species, further indicate that the secondary endosymbiont-mediated speciation is unlikely to have occurred in the B. tabaci species group.